Kahoot!-based evaluation instruments on acid-base materials - Dhiea Regita Cahyani; Dedeh Kurniasih; Raudhatul Fadhillah (Intelektual Pustaka Media Utama, 2022)
This research aimed to developed an evaluation instrument based on Kahoot! valid, practical, and reliable in evaluating student learning. This research is a model of development that use Borg and Gall. There were seven stages performed, starting with research and data collection, planning, product design development, initial field trials, review of initial trial results, main field trials, and refinement of field trial results. This research was conducted at Muhammadiyah 1 Pontianak Senior High School. As nine samples for the initial field trial and 29 samples involved for the main field trial. Three instruments developed by the researcher were validity, practicality, and reliability. The research data was obtained from the instrument as a result of the validation of materials experts and media experts, as well as questionnaires for teacher and student responses to the Kahoot! based evaluation instrument. The percentage of teachers and student responses to the instrument were 97.22% and 83.33%, respectively (very practical). Validation of materials experts and media experts with the respective percentages of 81.73% and 80.47% (very valid) and the obtained confidence value is 0.89 (very reliable). The results of this study indicated the instrument can be used in the evaluation of learning about acid-base materials.